ESTIMATION OF PARAMETER DEVIATION IN MODEL BASED ELECTRONIC CIRCUITS USING SLIDING MODE OBSERVER - , DZUHRI RADITYO UTOMO, Ir. Samiadji Herdjunanto, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
An estimator to estimate parameter deviation in a linear system is proposed. This estimator system is an observer-based estimator that uses Sliding Mode Observer. A sliding mode observer can be used to reconstruct the disturbance signal in a certain class of linear system. This property can be combined with the adaptive algorithm to estimate the deviation of the systemâs parameter model. Further application of this estimator is in electronic circuits. This estimator can be used to detect the parameter deviation in an electronic circuit, that has parameters which often change due to some internal and external causes. The proposed estimator has been simulated. It showed that in certain conditions it capable to estimate the deviation in the parameter of a linear system accurately. The proposed estimator has also been simulated using the linear model of an electronic circuit and provides a good estimation result.